Comparison of the structures and topologies of plasma extracted circulating nuclear and mitochondrial cell-free DNA - Pisareva, Ekaterina; Roch, Benoit; Sanchez, Cynthia; Pastor, Brice; Mirandola, Alexia; Diab-Assaf, Mona; Mazard, Thibault; Prévostel, Corinne; Al Amir Dache, Zahra; Thierry, Alain R. (Frontiers in Genetics, 2023)
Introduction: The function, origin and structural features of circulating nuclear DNA (cir-nDNA) and mitochondrial DNA (cir-mtDNA) are poorly known, even though they have been investigated in numerous clinical studies, and are involved in a number of routine clinical applications. Based on our previous report disproving the conventional plasma isolation used for cirDNA analysis, this work enables a direct topological comparison of the circulating structures associated with nuclear DNA and mitochondrial cell-free DNA. Materials and methods: We used a Q-PCR and low-pass whole genome sequencing (LP-WGS) combination approach of cir-nDNA and cir-mtDNA, extracted using a procedure that eliminates platelet activation during the plasma isolation process to prevent mitochondria release in the extracellular milieu. Various physical procedures, such as filtration and differential centrifugation, were employed to infer their circulating structures. Results: DSP-S cir-mtDNA mean size profiles distributed on a slightly shorter range than SSP-S. SSP-S detected 40-fold more low-sized cir-mtDNA fragments (<90 bp/nt) and three-fold less long-sized fragments (>200 bp/nt) than DSP-S. The ratio of the fragment number below 90 bp over the fragment number above 200 bp was very homogenous among both DSP-S and SSP-S profiles, being 134-fold lower with DSP-S than with SSP-S. Cir-mtDNA and cir-nDNA DSP-S and SSP-S mean size profiles of healthy individuals ranged in different intervals with periodic sub-peaks only detectable with cir-nDNA. The very low amount of cir-mtDNA fragments of short size observed suggested that most of the cir-mtDNA is poorly fragmented and appearing longer than ∼1,000 bp, the readout limit of this LP-WGS method. Data suggested that cir-nDNA is, among DNA extracted in plasma, associated with ∼8.6% of large structures (apoptotic bodies, large extracellular vesicles (EVs), cell debris…), ∼27.7% in chromatin and small EVs and ∼63.7% mainly in oligo- and mono-nucleosomes. By contrast, cir-mtDNA appeared to be preponderantly (75.7%) associated with extracellular mitochondria, either in its free form or with large EVs; to a lesser extent, it was also associated with other structures: small EVs (∼18.4%), and exosomes or protein complexes (∼5.9%). Conclusion: This is the first study to directly compare the structural features of cir-nDNA and cir-mtDNA. The significant differences revealed between both are due to the DNA topological structure contained in the nucleus (chromatin) and in the mitochondria (plasmid) that determine their biological stability in blood. Although cir-nDNA and cir-mtDNA are principally associated with mono-nucleosomes and cell-free mitochondria, our study highlights the diversity of the circulating structures associated with cell-free DNA. They consequently have different pharmacokinetics as well as physiological functions. Thus, any accurate evaluation of their biological or diagnostic individual properties must relies on appropriate pre-analytics, and optimally on the isolation or enrichment of one category of their cirDNA associated structures.